Patient with neuropsychiatric symptoms and insulinoma of difficult preoperative localization (2014)
This paper describes the case of a patient with neuropsychiatric symptoms who was diagnosed with hyperinsulinemic hypoglycemia with high suspicion of insulinoma, even after conventional diagnostic imaging was unable to locate it. A selective angiography of the pancreatic arteries and a calcium stimulation test were conducted to determine its location. The patient underwent a distal pancreatectomy using an intraoperative ultrasound, resulting in the disappearance of her symptoms.